2013
DOI: 10.1007/s10571-013-9918-7
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary Neurotrophic Factor Role in Myelin Oligodendrocyte Glycoprotein Expression in Cuprizone-Induced Multiple Sclerosis Mice

Abstract: Multiple sclerosis (MS) is an inflammatory disease of the central nervous system that leads to loss of myelin and oligodendrocytes and damage to axons. Myelin oligodendrocyte glycoprotein (MOG) is a minor component of the myelin sheath, but is an important autoantigen linked to the pathogenesis of MS. Ciliary neurotrophic factor (CNTF) has been shown to enhance the generation, maturation, and survival of oligodendrocytes in culture medium. The aim of this study was to demonstrate the role of CNTF on MOG expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Previous work using immunohistochemistry and Western blot showed that CNTF and FGF-2 are elevated for 4 wpi around the lesion border (Tripathi and McTigue, 2008); the present work extends this increased growth factor expression to 12 wpi. CNTF is an astrocyte-derived factor that promotes OL lineage cell survival, differentiation, and myelination (Barres et al, 1993(Barres et al, , 1996Mayer et al, 1994;Salehi et al, 2013;Vernerey et al, 2013). It initiates phosphorylation of STAT3 and enhances the effects of FGF-2, which is also important for oligodendrogenesis (Dell'Albani et al, 1998;Baron et al, 2000;Yokogami et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work using immunohistochemistry and Western blot showed that CNTF and FGF-2 are elevated for 4 wpi around the lesion border (Tripathi and McTigue, 2008); the present work extends this increased growth factor expression to 12 wpi. CNTF is an astrocyte-derived factor that promotes OL lineage cell survival, differentiation, and myelination (Barres et al, 1993(Barres et al, , 1996Mayer et al, 1994;Salehi et al, 2013;Vernerey et al, 2013). It initiates phosphorylation of STAT3 and enhances the effects of FGF-2, which is also important for oligodendrogenesis (Dell'Albani et al, 1998;Baron et al, 2000;Yokogami et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The role of ciliary neurotrophic factor (CNTF) in the process of remyelination has been demonstrat ed [22]. Here we show that daily administration of LIF significantly increases MOG and Opalin expres sion in the cuprizoneinduced mouse cerebral cortex.…”
Section: Discussionmentioning
confidence: 60%
“…Growth factors including insulin like growth factor were shown to be important in repair processes of demyelination [12]. Ciliary neurotrophic factor (CNTF) and leukemia inhibitory factor (LIF) have been shown to have an important role in the process of remyelination by increasing Opalin (34 KDa) and MOG expression [23,29]. It is suggested that the activation of MOG transcription depends more on an intrinsic oligodendroglial maturation program of myelination.…”
Section: Discussionmentioning
confidence: 99%